Sustainability Analysis of Green Open Space Development of Kupang City Nostalgic Park - Hendrik Toda; David Wilfrid Rihi; Ernawati Daeng; Adriana Rodina Fallo (Jurnal Multidisiplin Madani, 2023)
In the City of Kupang, East Nusa Tenggara Province, the development carried out by the government continues. One of them is the construction of a park which is a green open space for the community. One of the parks which is very popular as a recreation area in the City of Kupang is the Nostalgia Park, therefore researchers are interested in conducting research on the sustainability of the construction of green open spaces in the City of Kupang Nostalgia Park.The method utilized in this study is a descriptive research method with a qualitative approach, conducted in Kupang City with a total of 15 informants, and data gathering procedures include observation, interview, and document search techniques. The acquired data is then examined using data analysis techniques developed by Creswell (2016: 264-268). The sustainability of the development The Methodology in Sustainable Development Indicators (Department of Economic and Social Affairs, 2001: 14) was used to analyze the green open space in Nostalgia Park in Kupang City, which is described in three aspects with the findings on; (a) the social aspect with the construction of the City of Kupang Nostalgia Park can provide a positive social impact but is still constrained by theft and destruction of park facilities and infrastructure while from an economic aspect the c The availability of city parks as the city's lungs has been fulfilled in the framework of the development of the Kupang City Nostalgia Park